ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) IN ROBIN ROE’S NOVEL A LIST OF CAGES - Butar-Butar, Vivi Marianti (Lingual Journal of Language and Culture, 2020)
This thesis entitled "Attention Deficit Hyperactivity Disorder (ADHD) in Robin Roe's Novel A List of Cages" . This thesis discussed about the symptoms Attention Deficit Hyperactivity Disorder (ADHD) in the novel A List of Cages by Robin Roe. This thesis aimed to find out how the symptoms of ADHD are described through the leading character in the novel. This thesis used to describe the core symptoms of ADHD, namely: Attention, Impulsivity, and Hyperactivity. There are symptoms of ADHD that Adam has, namely: Attention symptom is easily bored; Impulsivity symptom is agitated; and the Hyperactivity symptom is: do excessive motor activities. This thesis used Russell Barkley's theory to analyze the symptoms in a novel using Literary Psychology. In analyzing this thesis, the writer used a qualitative descriptive method that presents all data in the form of words and sentences and uses library research as a way to collect data by reading and selecting quotations from the novel A List of Cages. From this research it is found that the leading character in the novel experienced all the three core symptoms of ADHD.